2021
DOI: 10.1002/anie.202108610
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of 9NHAc‐GD2 Antigen to Overcome the Hydrolytic Instability of O‐Acetylated‐GD2 for Anticancer Conjugate Vaccine Development

Abstract: Ganglioside GD2 is an attractive tumor-associated carbohydrate antigen for anti-cancer vaccine development. However,i ts lowi mmunogenicity and the significant side effects observed with anti-GD2 antibodies present significant obstacles for vaccines.T oo vercome these,anew GD2 derivative bearing an N-acetamide (NHAc) at its non-reducing end neuraminic acid (9NHAc-GD2) has been designed to mimic the 9-O-acetylated-GD2 (9OAc-GD2), aG D2 based antigen with ar estricted expression on tumor cells.9 NHAc-GD2 was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The 1440 copies per capsid are one of the highest ligand loading levels on Qβ reported to date. 18,19,26,27 MS sequencing of Qβ conjugated with lactoside 3 indicated high functionalization efficiency (80−100%) of lysines (K14, K17, K61, K64, and K68) on the capsid surface and moderate efficiency (46%) of the lysine K3 that lays between monomers in the capsid compared to almost no functionalization (∼1%) of K47, the S1).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The 1440 copies per capsid are one of the highest ligand loading levels on Qβ reported to date. 18,19,26,27 MS sequencing of Qβ conjugated with lactoside 3 indicated high functionalization efficiency (80−100%) of lysines (K14, K17, K61, K64, and K68) on the capsid surface and moderate efficiency (46%) of the lysine K3 that lays between monomers in the capsid compared to almost no functionalization (∼1%) of K47, the S1).…”
Section: ■ Resultsmentioning
confidence: 99%
“…2a1). [35][36][37] Abnormal expression or neo-expression of glycans on the surface of tumour cells in various cancer types provides promising epitopes for vaccine development. 38,39 Accordingly, glycopeptides have the potential for wide application in tumour therapy.…”
Section: Yan-mei LImentioning
confidence: 99%
“…Considering the translational relevance of GD2 and GD3 antigens for both canine and human melanomas, relevant veterinary studies of vaccination against these targets suggested their safety and ability to protect canine melanoma patients when provided as an adjunct to conventional therapies (86,88). Nevertheless, adjuvants and/or antigen modifications are needed to increase the immunogenicity of the vaccine to be successfully translated in a standard of care (88,89).…”
Section: Anti-cancer Vaccines For Omm Treatmentmentioning
confidence: 99%